2013
DOI: 10.1364/ol.38.003646
|View full text |Cite
|
Sign up to set email alerts
|

On the temporal behavior of Nd^3+ random lasers

Abstract: The temporal dynamics of random laser emission from Nd-doped crystal powders has been investigated by using an improved detection device. The precise conditions to detect high contrast, fast oscillations are described. The measured period is about one order of magnitude shorter than the one given in the literature for relaxation oscillations in these materials. The origin of these differences is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
5
10
0
Order By: Relevance
“…7(a). In this case, the output intensity essentially follows in time the pumping intensity (after build-up of the laser pulse), as observed in experiments [30], and in Fig. 7(b) [39].…”
Section: Results From the Numerical Model In The Temporal Domainsupporting
confidence: 62%
See 2 more Smart Citations
“…7(a). In this case, the output intensity essentially follows in time the pumping intensity (after build-up of the laser pulse), as observed in experiments [30], and in Fig. 7(b) [39].…”
Section: Results From the Numerical Model In The Temporal Domainsupporting
confidence: 62%
“…Although separate paths cannot be measured, we can measure the emission from small areas, of a size of the order of the distance of minimum transversal coherence, the transport length, which is about 10 microns. This can be achieved by using a lens that projects the image of the emitting surface on a plane where a pin-hole of the appropriate size [30] is placed. Under these conditions, no periodical fluctuations with a time range of tens of ps are detected.…”
Section: Results From the Numerical Model In The Temporal Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…We have observed that, in Nd stoichiometric crystal powders with a similar grain size, this delay time is much shorter [34,35]. In regular laser systems, this delay time between pump intensity and emission fluctuations is determined by the residence time of the photon inside the resonator [36].…”
Section: Resultsmentioning
confidence: 99%
“…A technical challenge is the high speed required for temporal modulation. Prior experimental studies with pulsed excitations have revealed fast dynamic response of random lasers [8][9][10][11][12][13][14][15][16][17][18][19][20], and the pump modulation needs to be on a comparable time scale.…”
Section: Introductionmentioning
confidence: 99%